Data-based differentiated instruction: The impact of standardized assessment and aligned teaching material on students' reading comprehension. (June 2022) - Karst, Karina; Bonefeld, Meike; Dotzel, Stefanie; Fehringer, Benedict C.O.F.; Steinwascher, Merle
Abstract: The paper analyzes the efficacy of a data-based differentiated instruction (DBDI) intervention in addressing growing achievement-related heterogeneity in school. The intervention consisted of a reading strategy training conducted by teachers, in which 27 secondary-school classes ( n students  = 656) participated. The propensity-matched control group consisted of another 27 classes ( n students  = 558). Linear mixed models showed that students of the intervention classes had no greater gain in reading competence on average compared to students of the control classes. However, the groups differed regarding the learning gain at different achievement levels. In the control group, the gain was greatest for the low achievers and lowest for the high achievers. This imbalance was not found in the intervention group, where the learning gain was similar for students of each achievement level. This shows that DBDI is a tool for addressing achievement-related heterogeneity which empowers teachers to cater to the differences between students. Highlights: Data-based differentiated instruction (DBDI) was implemented in 5th grade classes. DBDI is a tool for coping with achievement-related heterogeneity within a class. No main effect of DBDI on students' reading comprehension compared to control group. DBDI reduces the effect of initial performance level on learning gain. DBDI leads to nearly similar learning gains for students of each achievement level.